Rechargeable zinc nitrate / ethanol battery

By adopting molecular-metal relay catalytic strategy and tetraphenyl porphyrin (tpp) modified RhCu metalene (RhCu M-tpp) in zinc nitrate batteries, the problems of low energy density and poor rechargeability of zinc nitrate batteries are solved, and the battery performance of high energy density, long cycle life and low overpotential are achieved.

CN119786836APending Publication Date: 2025-04-08CITY UNIVERSITY OF HONG KONG
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202410887337.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2024-05-17
Filing Date
2024-07-03
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

Existing zinc nitrate batteries face the problems of limited energy density and poor rechargeability, making it difficult to achieve rechargeable batteries with high energy density and long cycle life.

Method used

Molecular-metal relay catalytic strategy was adopted to synthesize heterophase RhCu metalene (RhCu M-tpp) modified by tetraphenyl porphyrin (tpp) and optimize the electrolyte composition to achieve efficient NO3RR and ethanol oxidation reactions in neutral media.

Benefits of technology

High energy density (at least 110,000Wh kg-1cat), high power density (at least 1.5mW cm-2) and long-term cycle stability (about 400 times) are achieved, while reducing overpotential and improving ammonia Faraday efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119786836A_ABST
    Figure CN119786836A_ABST
Patent Text Reader

Abstract

The invention relates to a method for preparing an ultra-thin RhCu nanostructure modified by M-tpp and application of the ultra-thin RhCu nanostructure. By adjusting the feeding ratio of the raw materials, the form, composition, purity and size of RhCu M-tpp can be customized. The simplicity of operation and the robustness of reaction parameters contribute to high reproducibility of the target product. Furthermore, large-scale production can be achieved by proportionally increasing the concentrations of the metal ion precursor, reducing agent and surfactant, which reveals the huge potential of the molecule-modified ultra-thin RhCu nanostructures for industrial scale production.
Need to check novelty before this filing date? Find Prior Art

Description

CROSS-REFERENCE TO RELATED APPLICATIONS

[0001] This application claims priority to U.S. Provisional Patent Application No. 63 / 588,295 filed on October 6, 2023 and U.S. Patent Application No. 18 / 666,870 filed on May 17, 2024, and the disclosures of which are incorporated herein by reference in their entirety. Technical Field

[0002] The present invention relates to the field of electrochemical energy storage and catalysis. In particular, the present invention relates to surface molecular modification of ultrathin RhCu metalloene. Background Art

[0003] Zinc nitrate batteries have emerged as promising energy storage systems with the potential to revolutionize a variety of applications, including providing high energy supply, enabling ammonia (NH3) electrosynthesis, and facilitating wastewater treatment. These batteries are seen as competitive candidates for next-generation power accessories. However, current zinc nitrate batteries face technical barriers of limited energy density and poor rechargeability.

[0004] NH3 and its derivatives, such as fertilizers, are of great importance for the sustainable development of the Earth's biosphere. The nitrate reduction reaction (NO3RR) is regarded as a promising method for achieving high yields of NH3, which avoids the need for the harsh conditions (450-500°C, 200atm) and limited conversion percentages (10-20%) associated with the energy-intensive industrial Haber-Bosch process. Based on this, it is of great significance to construct a durable and eco-friendly secondary energy storage and conversion device that can be made from NO3 - / NO2 - The wastewater is treated to produce NH3 and at the same time output electricity to the external circuit.

[0005] According to the general working principle, the NO3RR activity of the cathode catalyst is determined by the assembled Zn-NO3 - Copper (Cu) is the most commonly used catalyst for NO3RR, which can convert NO3 to CO with relatively good Faradaic efficiency (FE). -Electrochemically converted into NH3. Existing technologies focus on optimizing the composition of Cu-based aggregates to improve the adsorption of protons on Cu, thereby reducing the overpotential of NO3RR, but these technologies still operate at a fairly negative applied potential (approximately -0.4 V to -0.7 V (relative to the reversible hydrogen electrode (RHE))) to ensure a moderate FE in a neutral medium (<-0.6 V, relative to RHE), and due to the rather low material utilization efficiency, the mass specific capacity is not satisfactory. At the same time, most existing Cu-based catalysts are designed for monofunctional NO3RR, so they are not suitable for oxidation reactions or are unstable for oxidation reactions. This makes the assembled zinc nitrate battery non-rechargeable, or the charging platform is large and the cycle life is quite limited.

[0006] On the other hand, most reported catalysts are designed for monofunctional NO3RR, and their poor electrocatalytic activity and structural stability toward oxidation reactions render the batteries non-rechargeable or with a large charging plateau and rather limited cycle life.

[0007] Zinc nitrate (Zn-NO3 - ) batteries have been considered as a promising option for next-generation power solutions, combining energy supply, ammonia electrosynthesis, and wastewater treatment into a single electrochemical device. 2+ / Zn redox couple (anodic reaction) combined After that, it can be established to process 1051Wh kg -1 Zinc nitrate battery with high theoretical energy density 1-2 Such self-powered metal-NO3 - The battery combines energy supply, NH3 electrosynthesis and wastewater treatment (e.g. removal of NO3 - ion pollutants), making the development of next generation high performance and eco-friendly power sources very attractive for distributed stationary energy storage and electric vehicles.

[0008] Guo, Ying et al. proposed a zinc nitrate battery configured in an H battery unit, wherein the zinc nitrate battery uses a Pd-doped TiO2 nanoarray supported by carbon cloth as the cathode 3 The cathode electrolyte consists of an aqueous mixture containing 0.25M LiNO3 and 5M LiCl, while the anode electrolyte comprises a 5M KOH solution. However, the battery is specifically designed to be discharged in the galvanic cell mode and is a non-rechargeable battery.

[0009] Existing zinc nitrate batteries are experiencing problems associated with low energy density and inadequate rechargeability. In view of these challenges, there remains a need in the art to develop rechargeable zinc nitrate batteries having both high energy density and extended cycle life. The present invention addresses these challenges. Summary of the invention

[0010] In this paper, a molecule-metal relay catalytic strategy is proposed to enhance the catalytic activity of NO3 in neutral solution at low overpotential. - Conversion into NH3.

[0011] The present invention also provides a method for synthesizing tetraphenylporphyrin (tpp) modified heterogeneous (amorphous / crystalline) tpp (RhCu M-tpp) and optimizing the electrolyte composition to achieve efficient NO3RR and ethanol oxidation reaction (EOR) in neutral medium. This method enables the development of rechargeable low overpotential and durable zinc nitrate / ethanol batteries.

[0012] In a first aspect, the present invention provides a rechargeable zinc nitrate / ethanol battery comprising a cathode having a conductive substrate coated with one or more copper-based catalysts, the one or more copper-based catalysts having a heterogeneous structure; an anode; a separator disposed between the cathode and the anode; an anolyte located on the anode side; and a catholyte located on the cathode side. The rechargeable zinc nitrate / ethanol battery exhibits at least 110,000 Wh kg -1 cat Energy density of at least 1.5 mW cm -2 The power density is as high as 1000 cycles and the long-term cycling stability is about 400 cycles.

[0013] In one embodiment, the one or more copper-based catalysts comprise a tetraphenylporphyrin-modified rhodium-copper alloy metalloene having a 2θ value of 41° to 42°.

[0014] In one embodiment, the tetraphenylporphyrin modified rhodium-copper alloy metalloene contains 60-85 wt % of Rh and 15-40 wt % of Cu.

[0015] In one embodiment, the tetraphenylporphyrin-modified rhodium-copper alloy metallographene exhibits micrometer-sized self-assembled networks with interconnected two-dimensional flexible nanosheets.

[0016] In one embodiment, at a low overpotential of less than -0.1 V, NO3 - Converted into NH3, the NO3 - First adsorbed and then reduced to NO2 on tetraphenylporphyrin - , and then NO2 -diffuses to the Cu site for subsequent hydrogenation process for NH3 production assisted by surrounding Rh atoms.

[0017] In one embodiment, the NH 3 generation rate of the tetraphenylporphyrin-modified rhodium-copper alloy metalloene increases with decreasing potential, and the NH 3 generation rate is nearly 6 times that of the unmodified rhodium-copper alloy metalloene.

[0018] In one embodiment, the tetraphenylporphyrin-modified rhodium-copper alloy metalloene exhibits two ethanol oxidation peaks at 0.8 V and 0.4 V compared to a reversible hydrogen electrode in an alkaline solution with an alcohol including EtOH, MeOH or ethylene glycol.

[0019] In one embodiment, the tetraphenylporphyrin-modified rhodium-copper alloy metalloene achieves an ammonia faradaic efficiency (FE) of at least 70% at a potential greater than -0.4V.

[0020] In one embodiment, the zinc nitrate / ethanol battery exhibits a high -2 The lower charging plateau is reduced by approximately 130 mV and normal function is maintained for at least 40 hours.

[0021] In one embodiment, the conductive substrate comprises conductive carbon cloth or a glassy carbon electrode.

[0022] In one embodiment, the anode comprises a zinc plate.

[0023] In one embodiment, the separator comprises a bipolar membrane.

[0024] In one embodiment, the anolyte comprises 1M KOH aqueous solution with 0.02M Zn(CH3COO)2, and the catholyte comprises 0.5M Na2SO4 / 3000ppm NO3 - A mixture of solution and 1 M ethanol.

[0025] In one embodiment, the heterogeneous structure comprises crystalline domains and amorphous domains.

[0026] In a second aspect, the present invention provides a method for synthesizing heterogeneous tetraphenylporphyrin-modified rhodium-copper alloy metalene. The method comprises co-reducing a rhodium (Rh) precursor and a copper (Cu) precursor in an oleylamine solution to obtain a RhCu metalene; adding at least one reducing agent and at least one surfactant to surface-modify the RhCu metalene; heating the RhCu metalene in an oil bath at 160° C. for 12 hours to obtain a modified RhCu metalene; subjecting the modified RhCu metalene to ligand exchange in chloroform in which tetraphenylporphyrin is dissolved, and centrifuging at 10,000 rpm for 5 minutes to obtain the heterogeneous tetraphenylporphyrin-modified rhodium-copper alloy metalene.

[0027] In one embodiment, the feed ratio of the Rh precursor to the Cu precursor is 8:1 based on molar amount.

[0028] In one embodiment, the heterogeneous tetraphenylporphyrin-modified rhodium-copper alloy metalloene has a thickness in a range of 0.01 nm to 1 nm.

[0029] In one embodiment, the tetraphenylporphyrin-modified rhodium-copper alloy metalloene contains 60-85 wt % of Rh and 15-40 wt % of Cu, and the element ratio of the Rh to the Cu is 4:1 based on molar amount.

[0030] In one embodiment, the at least one reducing agent comprises 1,2-butanediol and the at least one surfactant comprises potassium iodide.

[0031] In one embodiment, the ratio of the RhCu M to the tetraphenylporphyrin is 95:5.

[0032] In one embodiment, the heating is performed at a reaction temperature ranging from 155-180°C.

[0033] In one embodiment, the concentration of tetraphenylporphyrin is in the range of 5-100 mM.

[0034] The present invention has the following advantages: (1) The present invention combines catalyst design and optimized electrolyte to solve the above-mentioned problems. The synthesis procedure of RhCu M-tpp catalyst shows great prospects in large-scale production. At the same time, the proposed electrolyte optimization method is cost-effective, which can also have a positive impact on other advanced metal-catalyst coupled energy conversion and storage devices. (2) Experimental studies and density functional theory (DFT) calculations have demonstrated that the electroactivity of the interface between crystalline RhCu and amorphous RhCu is further enhanced by the introduction of TPP, thereby providing a wider range of active sites for nitrate reduction. The surface-bound TPP acts as a NO3 - Reduction to NO2 - The main active sites of the catalyst are the interface regions, while the subsequent reduction is accelerated through the interface region. This combined effect contributes to efficient electrocatalysis. (3) The RhCu M-tpp-based zinc nitrate / ethanol battery exhibits ultrahigh energy density, high power density, small discharge-charge voltage difference, and superior long-term cycling stability, which largely exceeds the performance of commercial Cu particle-based counterparts. Few existing metal-catalyst coupled aqueous batteries can exhibit such comprehensive performance and versatility. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] Embodiments of the present invention are described in more detail below with reference to the accompanying drawings, in which:

[0036] Figure 1A Schematic illustration of the synthesis steps of RhCu M-tpp and the working principle of the assembled zinc nitrate / ethanol battery is shown. Figure 1B The XRD pattern of the as-synthesized RhCu M-tpp is depicted. Figure 1C Highly magnified SEM images of the synthesized RhCu M-tpp and RhCuM are shown. Figure 1D Depicted are the EDS spectra of RhCu M-tpp and RhCu M. The inset shows the element ratio between Rh and Cu. Figure 1E The XRD pattern of the as-synthesized RhCu M-tpp is shown. Figure 1F EELS spectra of RhCu M-tpp, RhCu M, and carbon supports in Cu grids are depicted;

[0037] Figure 2 FT-IR spectra of commercial tpp powder (upper) and as-synthesized RhCu M-tpp (lower) are depicted;

[0038] Figures 3A-3D A typical low-dose HAADF-STEM image of RhCu M-tpp is shown;

[0039] Figures 4A-4C A low-dose HAADF-STEM image extracted at 1 Pa showing crystalline and amorphous domains within the RhCu M-tpp in-plane structure is shown, along with a selected area FFT map attributed to the domains. Figure 4Dshows a magnified HAADF-STEM image showing crystalline and amorphous domains;

[0040] Figures 5A-5D HAADF-STEM images and corresponding elemental mapping of Rh, Cu, and N of RhCu M-tpp are depicted;

[0041] Fig. 6A Normalized Cu K-edge XANES spectra of RhCu M-tpp, RhCu M, and Cu NPs are depicted. Inset: A zoomed-in view of the detailed white line position. Data for reference samples of Cu foil, Cu2O, and CuO are included for comparison. Figure 6B The R-space EXAFS of RhCu M-tpp, RhCu M, and Cu NPs are depicted. Figure 6C The fitting results of the EXAFS spectrum of RhCu M-tpp at the Cu K-edge are depicted. Fig.6D The R-space EXAFS fittings of RhCu M-tpp, RhCu M, and Cu NPs are depicted;

[0042] Fig. 7A Wavelet transforms of RhCu M-tpp, RhCu M and Cu NPs are shown. Figure 7B Wavelet transform of CuK-edge EXAFS spectra of Cu foil and CuO is shown;

[0043] Fig. 8A Survey XPS spectra of RhCu M-tpp, RhCu M, and Rh M are depicted. Figure 8B High-resolution Rh 3d XPS spectra of RhCu M-tpp, RhCu M, and Rh M are depicted;

[0044] Fig. 9A High-resolution XPS spectra of Cu 2p of RhCu M-tpp, RhCu M, and Cu NPs or tpp are depicted. Fig. 9B Cu LMM AES spectra of RhCu M-tpp, RhCu M, and Cu NPs are depicted. Fig. 9C High-resolution XPS spectra of N1s of RhCu M-tpp, RhCu M, and Cu NPs or tpp are depicted;

[0045] Fig.10 Figure 3 shows the effects of RhCu M-tpp, RhCu M, Rh M and Cu NPs in the presence (solid line) and absence (dashed line) of 3000 ppm NO3. - In a neutral 0.5M Na2SO4 solution at 5mV s -1 The LSV curve below;

[0046] Fig.11 Figure 3 shows the NH3 and NO2 on RhCu M-tpp, RhCu M, Rh M, and Cu NPs at different applied potentials. - FE;

[0047] Fig.12 The NH3 production rates on RhCu M-tpp, RhCu M, Rh M, and Cu NPs at different applied potentials are depicted;

[0048] Figures 13A-13C The CA curves of RhCu M-tpp, Rh M and Cu NPs at different applied potentials are depicted. Fig.13D The NH3 partial current density of RhCu M-tpp, RhCu M, Rh M and Cu NP at the aforementioned potentials is depicted;

[0049] Fig.14A The double layer capacitance (C dl )’s fitting results. Fig. 14B The results show that the RhCu M-tpp and RhCu M cathodes were charged at 20 mV s -1 , 40mV s -1 , 60mV s -1 , 80mV s -1 and 100mV s -1 The cyclic voltammetry curve close to OCP was obtained at a scan rate of

[0050] Fig.15 Depicting the use of RhCu M-tpp 14 NO3 - or 15 NO3 - The NH3 production was quantified by both UV-vis and NMR methods after electrolysis at -0.2 V (vs. RHE) as a nitrogen source for 1 hour. The yield of NH3 in the absence of an applied potential but in the presence of NO3 is also provided. - And no NO3 - The amount of NH3 recorded at -0.2 V (vs. RHE) in the case of 14 NO3 - or 15 NO3 - The electrolyte after NO3RR 1 H NMR spectroscopy;

[0051] Fig.16Plotted are the FE and production rate of NH3 on RhCu M-tpp during 6 cycles of electrolysis at −0.2 V (vs. RHE) for 1 h.

[0052] Figures 17A-17B The curves of RhCu M-tpp and RhCu M in 1 M KOH solution and 1 M KOH + 1 M EtOH solution at 50 mV s -1 CV curves in the potential window of 0.05–1.1 V (vs. RHE) are shown below. Fig. 17C Depicted are chronoamperometric curves of RhCu M-tpp and RhCu M tested in 1 M KOH + 1 M EtOH at 1 V (vs. RHE) for 3600 s. Fig.17D The mass activities of RhCu M-tpp and RhCu M at 0.8 V (vs. RHE) (left) and at 1 V (vs. RHE) at 1800 s (right) are depicted;

[0053] Figures 18A-18C Shown is a low magnification HAADF-STEM image showing the morphology of RhCu M-tpp after EOR testing. Fig.18D A high magnification HAADF-STEM image showing porous and ultrathin metalloene nanostructures is shown. Fig.18E Shown is an atomic resolution HAADF-STEM image depicting the amorphous domains of RhCu M-tpp after EOR testing in 1M KOH+1M EtOH solution. Fig.18F shows an atomic resolution HAADF-STEM image depicting the crystalline domains of RhCu M-tpp after EOR testing in 1 M KOH + 1 M EtOH solution;

[0054] Fig.19A Depicted is the assembled Zn-NO3 using RhCu M-tpp with conventional electrolyte in the absence of ethanol. - OCV curve of the battery within the first 24 hours. Fig.19B Depicted is the assembled Zn-NO3 using RhCu M-tpp with conventional electrolyte in the absence of ethanol. -f The rate capability of the battery during the discharge process;

[0055] Fig. 20A Depicts Zn-NO3 - OCV curves of a primary cell (using electrolyte without ethanol) and a rechargeable zinc nitrate / ethanol cell (using electrolyte with ethanol) over the initial 24 hours. Fig. 20B Depicts Zn-NO3- Rate performance of primary cells (using electrolyte without ethanol) and rechargeable zinc nitrate / ethanol cells (using electrolyte with ethanol) during discharge;

[0056] Fig.21A The rate performance of ZnNO3 / ethanol batteries with RhCu M-tpp and Cu NPs during discharge is depicted. Fig. 21B The ZnNO3 / ethanol battery with RhCu M-tpp cathode is shown in Figure 2 at 0.1 mA cm -2 and 0.5mAcm -2 From OCV to 0.005V (relative to Zn 2+ Inset: A digital photograph showing the constructed battery device and the OCV measurement results. Fig. 21C The discharge polarization curves and the resulting power density curves of the zinc nitrate / ethanol cells using RhCu M-tpp and Cu NPs are depicted. Fig.21D Depicted are the LSV curves of the RhCu M-tpp cathode after NO3RR from 0.6 V to 1.8 V (vs. RHE) in the electrolyte with and without ethanol. Inset: Digital photographs of the reaction phenomena on the electrode during the anodic scan with (right) and without (left) ethanol, respectively;

[0057] Fig. 22 The voltage difference as a function of current density is shown. The voltage difference between the anode LSV curves (ΔV = VOER - VEOR) is attributed to the Zn-NO3 using the electrolyte without ethanol and the electrolyte with ethanol. - Battery;

[0058] Fig.23A The round-trip discharge-charge curves of the zinc nitrate / ethanol battery with RhCu M-tpp at different current densities are depicted. Fig. 23B The discharge-charge curves of the RhCu M-tpp-based zinc nitrate / ethanol battery at different current densities are depicted. Fig.23C Depicted are the calculated energy efficiencies of RhCu M-tpp based zinc nitrate / ethanol batteries. Fig.23D Long-term cycling stability tests of the thus assembled zinc nitrate / ethanol and zinc nitrate batteries are depicted. Fig.23E The long-term cycling stability at high rates is depicted. The constructed RhCu M-tpp-based rechargeable ZnNO3 / ethanol battery has a high cycling stability at 0.5 mA cm -2 (equal to 1.25A gcat -1) under the electrochemical behavior. Each cycle contains a 5-minute constant current discharge and a subsequent 5-minute recharge, and the battery can stably last for about 400 cycles;

[0059] Fig.24A The HAc concentrations of 0 ppm, 2.5 ppm, 5 ppm, 7.5 ppm, 10 ppm, 15 ppm and 20 ppm are plotted. 1 H NMR spectroscopy. Fig. 24B Calibration curves for solutions with given HAc concentrations are plotted. Fig.24C The cathode electrolyte after dilution 60 times is depicted. 1 H NMR spectrum extracted from a rechargeable zinc nitrate / ethanol cell at the 300th cycle. Fig.24D The HAc concentration, HAc increase rate and corresponding energy efficiency of the battery at selected cycles are depicted;

[0060] Fig.25 The electrolytes used are depicted in pristine, discharged, and charged states. 1 H NMR spectroscopy;

[0061] Fig.26A Depicted are typical TEM images of RhCu M-tpp after long-term cycling. Fig.26B Depicted are HRTEM images of RhCu M-tpp after long-term cycling. Fig.26C Depicted is the EDS spectrum of RhCu M-tpp after long-term cycling testing. Inset: Table showing the elemental ratio between Rh and Cu. Fig.26D High-resolution Rh 3d and Cu 2p XPS spectra of the RhCu M-tpp cathode extracted from a zinc nitrate / ethanol cell after long-term cycling testing are depicted;

[0062] Fig.27A Figure 3 shows the potentials of pure tpp, RhCu M and RhCu M-tpp at different applied potentials. ratio. Fig.27B The charge consumption rate of NO3RR normalized to ECSA of RhCu M-tpp and RhCu M at different potentials is depicted;

[0063] Fig.28A Depicted is the in situ DEMS profile of the RhCu M-tpp cathode during NO3RR in 0.5M Na2SO4+3000ppm NaNO3. Five cycles of cathode LSV from 0.2V to -0.7V (vs. RHE) were repeated to improve detection reliability. Figures 28B-28C Depicts a digital photograph depicting a- and NH3 quantification ( Fig.28B ) and gaseous H2 quantification ( Fig.28C ) using H battery cells in different configurations. Fig.28D Faradaic efficiencies of RhCu M-tpp and RhCu M cathodes for H2 during NO3RR at -0.2 V and -0.5 V (vs. RHE) are plotted.

[0064] Fig.29 The surface potential distribution map of RhCu M-tpp is shown;

[0065] Fig.30 The potential line scan of RhCu M-tpp is depicted;

[0066] Figures 31A-31B The initial NO3RR ( Fig.31A ) and subsequent EOR( Fig.31B ). Four cycles of cathodic and anodic LSV scans were performed to drive the electrocatalytic reaction;

[0067] Fig.32 In situ DEMS images of the RhCu M-tpp cathode during three cycles of ordered cathode (NO3RR) and anode (EOR) LSV scans are depicted. -1 Under, the cathode LSV is carried out from 0 V to -0.66 V (relative to RHE), and the anode LSV is carried out from 0.551 V to 1.6 V (relative to RHE);

[0068] Fig.33A A 3D contour map of the electron distribution near the Fermi level of RhCu M-tpp is shown. Fig.33B A 3D contour map of the electron distribution close to the Fermi level of RhCu M is shown. Fig.33C The PDOS of RhCu M-tpp is depicted. Fig.33D Depicted NO3 on RhCu M-tpp - Adsorbed PDOS. Fig.33E Site-dependent PDOS of Cu-3d in the crystalline and amorphous parts (left two panels) and Rh-4d in the crystalline and amorphous parts (right two panels) in RhCu M-tpp are shown. Fig.33F Depicted is the comparison of reaction energies for nitrate reduction on RhCu M-tpp and RhCu M. Figure 33GComparison of adsorption energies of key intermediates on different sites of RhCu M-tpp is depicted. IF = interface, crystalline = crystalline part of RhCu, amorphous = amorphous part of RhCu; and

[0069] Fig.34 A digital photograph showing a commercial digital clock powered by a constructed zinc nitrate / ethanol battery to operate continuously for over 24 hours. DETAILED DESCRIPTION

[0070] Metal-based nanomaterials have sparked great research interest in the field of clean energy. Currently, lithium-ion batteries (LIBs) are the main choice for powering portable electronic devices and stationary energy storage devices. Nevertheless, due to their limited energy storage capacity and the limited reserves of cobalt and lithium on Earth, the further development of LIBs faces challenges. The development of next-generation high-energy-density secondary battery systems with environmental friendliness is a major contribution. However, the relevant research is still in its early stages, which makes it crucial to establish a promising technological foundation that can pave the way for subsequent industrialization.

[0071] In general, most Cu-based catalysts exhibit optimal performance for NO3RR at fairly negative applied potentials (approximately -0.4 V to -0.7 V (vs. RHE) in alkaline solutions and more negative, approximately -0.6 V to -1.2 V (vs. RHE) in neutral solutions) due to the weak adsorption of protons by Cu. 4-5 To achieve this, a significant overpotential is required to enhance the proton coverage on the Cu surface and overcome the high energy barrier for hydrogenation. - / NH3 and anode Zn 2+ / The equilibrium potential gap between Zn pairs (i.e., Zn-NO3 - On the other hand, due to the limited atomic utilization efficiency of large-sized Cu aggregates, the ammonia production rate is still unsatisfactory. This limitation seriously affects the mass specific capacity of the cathode catalyst. Due to these problems, the assembled Zn-NO3 - The practical energy density of the battery is significantly suppressed. Achieving sufficient Faradaic efficiency (FE) of NH3 in the low overpotential range (e.g., potential > -0.4 V vs. RHE) remains a major challenge, especially in neutral electrolytes.

[0072] Thus, the present invention provides a high-performance rechargeable zinc nitrate / ethanol battery in an H-cell, in which the heterogeneous RhCu M-tpp acts as a bifunctional catalyst for efficient NO3RR (discharge) and EOR (charge) in a cathode neutral electrolyte, while the zinc (Zn) plate acts as a metallic anode in an anodic alkaline electrolyte. NO3RR is highly efficient due to the relatively low bond energy of N=O (204 kJ mol -1 ) and nitrate (NO3 - ) and is considered to be a promising method for producing NH3 at a high production rate.

[0073] In one embodiment, a rechargeable zinc nitrate / ethanol battery comprises a cathode, an anode, a separator disposed between the cathode and the anode, an anolyte on the anode side, and a catholyte on the cathode side.

[0074] In one embodiment, the cathode is made of a conductive substrate coated with one or more copper-based catalysts having a heterogeneous structure. The one or more copper-based catalysts may include tetraphenylporphyrin-modified rhodium-copper alloy metalloene. The tetraphenylporphyrin-modified rhodium-copper alloy metalloene exhibits a micrometer-sized self-assembled network with interconnected two-dimensional flexible nanosheets.

[0075] In one embodiment, the heterogeneous structure includes crystalline domains and amorphous domains. The iodide ions act as both complexing agents and capping agents, which induce the formation of two-dimensional (2D) nanostructures rather than zero-dimensional (0D) nanostructures.

[0076] The NH3 generation rate of tetraphenylporphyrin-modified rhodium-copper alloy metalloene increases with decreasing potential (up to 717.8 mg h -1 g -1 cat The maximum point of the NH3 production rate is nearly 6 times that of the unmodified rhodium-copper alloy metalloene.

[0077] In addition, in an alkaline solution with alcohol, the tetraphenylporphyrin-modified rhodium-copper alloy metalloene exhibited two ethanol oxidation peaks at 0.8 V and 0.4 V compared to the reversible hydrogen electrode, and the alcohols included EtOH, MeOH or ethylene glycol. Ethanol (EtOH) was added to the NO3RR electrolyte to replace OER with ethanol oxidation reaction (EOR) in order to enhance the energy economy during charging.

[0078] In one embodiment, the alkaline solution may include 1 M KOH aqueous solution.

[0079] The tetraphenylporphyrin-modified rhodium-copper alloy metalloene achieves an ammonia faradaic efficiency (FE) of at least 70% at a potential above -0.4 V. The highest ammonia FE can be 84.8% at -0.2 V (vs. RHE).

[0080] Specifically, the tetraphenylporphyrin-modified rhodium-copper alloy metalloenide contains 10-20 wt % Cu and 70-85 wt % Rh.

[0081] Preferably, the tetraphenylporphyrin modified rhodium-copper alloy metalloene contains 15 wt % Cu and 84.38 wt % Rh.

[0082] NO3 is generated at a low overpotential below -0.1V - Converted into NH3, the NO3 - First adsorbed and then reduced to NO2 on tetraphenylporphyrin - , then NO2 - diffuses to the Cu site for subsequent hydrogenation assisted by surrounding Rh atoms to produce NH3.

[0083] In one embodiment, the conductive substrate can be a conductive carbon cloth or a glassy carbon electrode. The anode can be a 2 cm2 x 2 cm2 zinc plate manufactured by Sheng Er Nuo Co. LTD or any commercially available zinc plate. The diaphragm can be a bipolar membrane. For example, a Φ2.5 cm FBM-PK manufactured by Sheng Er Nuo Co. LTD or a BMS manufactured by Membrane Technology & Research, Inc or any commercially available bipolar membrane.

[0084] In one embodiment, the electrolyte can be customized according to the type of organic ammonia compound required. For example, the anolyte includes a 1M KOH aqueous solution with 0.02M Zn(CH3COO)2, and the catholyte includes 0.5M Na2SO4 / 3000ppm NO3 - The salt can be replaced by other common alkali metal salts, such as Li2SO4, K2SO4, LiNO3, KNO3, etc. or a mixture thereof. In addition, small molecule alcohols, such as methanol, glycerol and benzyl alcohol can also replace C2H5OH and play a similar role in oxidation in the electrolyte.

[0085] The rechargeable zinc nitrate / ethanol battery exhibits at least 110,000 Wh kg -1 cat Energy density of at least 1.5 mW cm -2The power density of the battery is 117364.6Wh kg, and the long-term cycling stability is about 400 cycles. -1 cat The excellent energy density, superior rate capability, outstanding cycling stability for at least 400 cycles, and ammonium acetate yield are demonstrated.

[0086] In a second aspect of the invention, a simple one-pot wet chemical growth and ligand exchange method using commercial chemicals and easily accessible equipment is provided. The morphology, composition, purity and size of the RhCu M-tpp can be adjusted by varying the feed ratio of the raw materials. Large-scale production can be achieved by proportionally scaling up the concentrations of metal ion precursors, reducing agents and surfactants, revealing the high feasibility of industrial-level production of molecularly modified ultrathin RhCu nanostructures.

[0087] RhCu M-tpp is prepared by a simple ligand exchange method. Typically, RhCu metalloene (RhCu M) is dispersed in chloroform containing tetraphenylporphyrin (tpp). The slurry is kept stirred at room temperature for 24 hours to perform sufficient ligand exchange. Finally, the sediment can be collected by centrifugation and washed several times with a chloroform / ethanol (v / v=1 / 1) solution.

[0088] In one embodiment, the ratio of the RhCu M to the tetraphenylporphyrin is 95:5.

[0089] In one embodiment, the concentration of tetraphenylporphyrin is in the range of 5-100 mM.

[0090] The outstanding bifunctionality of the RhCu M-tpp catalyst used in these cells helps to enhance operating efficiency and energy conservation by increasing energy density and reducing discharge-charge overpotential in these devices. In addition, by changing the type of alcohol added, the recycled electrolyte can produce several value-added ammonium salts. Rechargeable metal-nitrate / alcohol batteries, which constitute the main potential application of the present invention, have great appeal as future high-performance and environmentally friendly power sources for distributed stationary energy storage and electric vehicles.

[0091] Examples

[0092] Example 1

[0093] Materials and methods

[0094] Chemicals and Materials

[0095] Rhodium acetylacetonate (Rh(acac)3, 97% metal base), copper acetylacetonate (Cu(acac)2, ACS reagent, ≥99.5%), tetraphenylporphyrin (tpp, 95%), potassium iodide (KI, AR), oleylamine (OAm, 70%, technical grade), n-hexane (anhydrous, 99.5%), and ethanol (anhydrous, ≥99.9%) were purchased from Sigma-Aldrich. 1,2-Butanediol (1,2-BDO, 99.5%, AR), sodium sulfate (Na2SO4), sodium nitrate (Na 14 NO3, anhydrous, ≥99.0%) 15 N-labeled sodium nitrate (Na 15 NO3, anhydrous, ≥99.0%), deuterium oxide (D2O, 99.9%) at D), sodium hydroxide (NaOH, >98%), salicylic acid (C7H6O3, 99%), acetic acid (CH3COOH, HAc, >97%), sodium citrate (C6H5Na3O7, AR), sodium nitrosoferrocyanide dehydrate (C5FeN6Na2O·2H2O, 99%), hydrogen peroxide (H2O2, 30%), maleic acid (C4H4O4, 98%), sodium hypochlorite solution (NaClO, AR, active chlorine 6-14%) wt ) and other chemicals not specifically mentioned were purchased from Aladdin. Carbon paper (Toray TGP-H-060), Nafion solution (5% wt ), Nafion 117 membrane and bipolar membrane were purchased from Fuel Cell Earth. Ultrapure Milli-Q distilled water (Milli-Q system, Millipore) was used in the experiment. All chemicals were used as received without any further purification.

[0096] Electrocatalytic measurements

[0097] Before the electrochemical measurements, the Nafion 117 membrane was immersed in 5% wt The catalyst was immersed in H2O2 for 1 hour and then immersed in distilled water at 80°C for another 1 hour for activation and purification. All NO3RR performances were evaluated in ambient environment in H cell cells separated by activated Nafion 117 membranes. CP-supported catalyst, Ag / AgCl electrode and platinum (Pt) plate (1×1 cm 2) were used as working electrode, reference electrode and counter electrode, respectively. Ar-saturated solution containing 0.5 M Na2SO4 and 3000 ppm NaNO3 served as both cathode electrolyte and anode electrolyte. Note that all working electrodes were subjected to cyclic voltammetry (CV) scans in 0.5 M Na2SO4 within a potential window of -0.351 V to -1.351 V (relative to RHE) for 60 cycles. The three-electrode system was used in the presence or absence of NO3 - In the electrolyte at 5mV s -1 LSV measurements were performed at a scan rate of 1.3 Å. Chronoamperometry (CA) tests were performed in a typical H-cell with 25 mL electrolyte in the anode and cathode sides at a stirring rate of 600 rpm at a series of different applied potentials with 85% IR compensation to accelerate mass transfer.

[0098] All electrochemical measurements were performed on an Ivium electrochemical workstation (Ivium-n-Stat, Netherlands). Unless otherwise specified, all potentials in the present invention are referenced to RHE according to the following formula: E(RHE)=E(Ag / AgCl)+0.197+0.059×pH.

[0099] In situ differential electrochemical mass spectrometry (DEMS) was performed on a Linglu DEMS analysis system in a specially designed probe-type DEMS cell, where a glassy carbon electrode coated with a RhCu M-tpp electrocatalyst, a Pt wire, and a saturated Ag / AgCl electrode were utilized as the working, counter, and reference electrodes, respectively.

[0100] For NO3RR, at 6 mV s -1 Four cycles of cathode LSV from 0 V to -0.66 V (vs. RHE) were performed to drive the reaction. There were rest intervals between adjacent LSV processes before the NH3 signal recovered to the initial state. After recording the data, the assembled probe-type DEMS cell underwent 2 h of electrocatalysis at -0.851 V (vs. RHE) to simulate NH3 production during discharge. Next, the NH3 was electrocatalyzed at 6 mV s -1 Four more cycles of anodic LSV from 0.551 V to 1.6 V (vs. RHE) were performed to achieve EOR. By monitoring the signal changes of the target mass-to-charge ratio, the intermediates and products formed in different electrochemical processes can be identified.

[0101] Determination of ammonia and nitrite

[0102] In order to determine the amount of NH3 produced after NO3RR for 1 hour under various conditions, the indophenol blue method was used. In detail, 1 mL of electrolyte was taken out after the test and diluted with distilled water at an appropriate multiple. First, 2.5 mL of solution A (composed of 0.625 M NaOH, 0.36 M salicylic acid, and 0.17 M sodium citrate) was added. Then, 300 μL of solution B (sodium nitrosoferricyanide, 10 mg mL -1 ) and 150 μL of solution C (NaClO, active chlorine 6-14% wt ). It was then subjected to sufficient vortexing for homogeneous mixing, and then kept undisturbed for 3 hours at ambient environment. Next, UV-vis spectrophotometry was used to check the absorbance value of these mixed solutions at 660 nanometers, and the NH3 concentration could be obtained according to the standard curve. The amount of NH3 generated was also measured by 1 Calculation by H NMR method. 10 μL C4H4O4 was added to 1 mL of electrolyte after NO3RR to serve as a quantitative reference. After that, 50 μL of 4M H2SO4 was further introduced to provide a weak acid environment. Subsequently, 50 μL of D2O was added to 450 μL of the above mixed solution for NMR measurement. Calculation of NH4 + The integrated peak area ratio between C4H4O4 and NH4 + Concentration. Standard NH4 with a given concentration of (NH4)2SO4 was prepared in 0.05M H2SO4 + Solution to establish the calibration curves for UV-vis and NMR methods. 15 For N labeling experiments, in addition to using 15 Except for the use of NaNO3 as the nitrogen source, all electrochemical operations and quantitative analyses were the same.

[0103] In order to determine NO2 - After the test, 1 mL of electrolyte was taken out and diluted with distilled water at an appropriate multiple. Then, 10 μL of N-(1-naphthyl)ethylenediamine dihydrochloride solution (10 mg mL -1 ) was dripped into the diluted electrolyte. After 20 minutes, these solutions were measured by UV-vis spectrophotometry. The absorbance at 540 nm was recorded to calculate NO2 according to the standard curve. - The standard calibration curve can also be obtained by using a standard NO2 with a given concentration of NaNO2 - Solution to obtain.

[0104] NH3 and NO2 - The Faradaic efficiency (FE) and weight-normalized production rate were calculated by the following equations: FE(NH3)=(8×F×M×V×D n ) / Q NH3 production rate = (17 × M × V × D n ) / (t×W) Where F is the Faraday constant (96485C mol -1 ), M is NH3 or NO2 - is the measured concentration of, V is the volume of electrolyte used (0.025 L), Q is the total amount of charge transferred during NO3RR, and D n is the dilution factor, t is the reaction time, and W is the mass loading of the working electrode.

[0105] Electrocatalytic EOR measurements

[0106] All EOR performances were evaluated for NO3RR tests using the same H cell unit. CP-supported catalysts, Ag / AgCl electrodes, and platinum (Pt) plates (1 × 1 cm 2 ) were also used as working electrode, reference electrode and counter electrode, respectively. Before the measurement, all working electrodes were activated by CV scanning for 60 cycles in a potential window of 0.05-0.8V (relative to RHE) in Ar-saturated 1M KOH. After that, the EOR performance was tested in a potential window of 0.05-1.1V (relative to RHE) in a mixture of 1M KOH and 1M EtOH with stirring at 600rpm. CA tests were performed at 1V (relative to RHE) with 85% IR compensation in a typical H cell with 25mL electrolyte in the anode and cathode sides.

[0107] Determination of acetic acid (HAc)

[0108] pass 1 The H NMR method calculates the amount of HAc produced during the cycling of zinc nitrate / ethanol batteries. First, 1.5 mL of cathode electrolyte is taken out from the battery after a given cycle and diluted with distilled water at an appropriate multiple. After that, 30 μL of DMSO / D2O mixture is added to 600 μL of the diluted solution, in which DMSO serves as a quantitative reference for NMR measurements. The integrated area ratio between the HAc peak and the DMSO peak is calculated, and the corresponding HAc concentration can be calculated based on the calibration curve. A standard HAc solution of a given concentration is prepared to obtain a standard curve, and then a calibration curve is established accordingly by the NMR method.

[0109] Characterization

[0110] The electron dose is reduced to FT-IR spectra were recorded using KBr pellets on a Bruker TENOR 27 spectrophotometer. Product analysis was performed using nuclear magnetic resonance spectroscopy (NMR 300 MHz, Bruker AVANCE Ⅲ BBO probe) and ultraviolet-visible absorption spectroscopy (UV-vis spectrophotometer, SHIMADZU UV-2600). X-ray absorption spectroscopy (XAS) was performed in transmission mode at the particle beam X-ray absorption fine structure (XAFCA) for catalysis at the Singapore Synchrotron Light Source. XAS-related data processing was performed using Athena and Artemis software packages. Extended X-ray absorption fine structure (EXAFS) fitting was performed using Artemis in R space. The coordination parameters of the sample were obtained by fitting the experimental peaks to the theoretical amplitudes. Quantitative curve fitting was performed for all samples, with the R range being And the range of k is The backscattering amplitude F(k) and phase shift Φ(k) are calculated by FEFF6.0 code. For curve fitting, all amplitude reduction factors S0 2 It was set to the best fit value of 0.92, which was determined by fitting the data for copper foil by fixing the coordination number as a known crystallographic value.

[0111] DFT calculations

[0112] DFT calculations based on the CASTEP package have been introduced to study the electronic modulation induced by the tpp molecules in RhCu M. Specifically, the generalized gradient approximation (GGA) and the Perdew-Burke-Ernzerhof (PBE) functional are applied to treat the exchange-correlation interaction. Ultrasoft pseudopotentials have been selected and the corresponding plane wave basis cutoff energy is set to 440 eV with the hyperfine quality. In the present invention, for all energy minimizations, the Broyden-Fletcher-Goldfarb-Shannon (BFGS) algorithm is applied under the k-point setting of the rough quality with a separation of The following convergence criteria are applied to all geometry optimizations, where the Hellmann-Feynman force should be less than And the total energy difference should converge to less than 5×10 -5 eV / atom.

[0113] Theoretical calculations

[0114] To construct the crystalline part of RhCu M, the (110) surface was cut from the Rh unit cell with 6 atomic layers, in this case less than 1 nm thick to match the experiment. 25% of the Rh sites have been replaced by Cu atoms to match the 3:1 atomic ratio. For the amorphous part of RhCu M, molecular dynamics (MD) simulations were performed at 1200 K for 5 picoseconds with 1 femtosecond per step. The MD simulations were performed under NVT conditions using constant temperature and volume. RhCu M is constructed from a semi-crystalline part and a semi-amorphous part with a total of 120 atoms (Rh 90 Cu 30 Considering the large size of tpp molecules, the building blocks of tpp were introduced only at the interface within RhCu M. of vacuum space to ensure sufficient space during the relaxation process.

[0115] Example 2

[0116] Synthesis of heterogeneous RhCu M-tpp nanostructures

[0117] The present invention provides a simple one-pot wet chemical growth method that utilizes commercially available chemicals and readily available equipment. The synthesis process of RhCu M-tpp is schematically shown in Figure 1A The synthesis routine can be divided into two steps. The slow co-reduction of Rh precursor and Cu precursor in oleylamine assisted by reducing agent and surfactant leads to the formation of ultrathin amorphous / crystalline RhCu bimetallic metalloene (RhCu M). In the subsequent step, the obtained RhCu M is subjected to ligand exchange in chloroform dissolved with tpp molecules. The phase composition, morphology and size of RhCu M-tpp can be controlled by adjusting the reaction temperature and the feed ratio of Rh / Cu precursor. All starting chemicals are available from commercial companies.

[0118] In a typical synthesis scheme of amorphous / crystalline RhCu M, 3200 μL OAm, 800 μL Rh (acac) 3 solution (5 mM in OAm) and 400 μL KI solution (40 mM in 1,2-BDO) were first mixed together in a 20 mL glass vial, and then stirred for 10 minutes. After this, 200 μL Cu (acac) 2 solution (5 mM in OAm) was added, and then stirred for another 10 minutes to ensure that the solution was homogeneous and transparent, and then the magnetic stirring bar was removed. Then, the sealed glass bottle was subjected to heat treatment in an oil bath at 160 ° C for 12 hours. After cooling to room temperature, the sediment was collected by centrifugation at 10000 rpm for 3 minutes, and the sediment was washed three times with a mixture of n-hexane and ethanol in a volume ratio of 1: 1. The final RhCu M product was stored in n-hexane for further use.

[0119] In a typical ligand exchange process for preparing heterogeneous RhCu M-tpp, the obtained RhCu M is first ultrasonically treated in chloroform for 10 minutes, and then collected by centrifugation at 10,000 rpm for 10 minutes. Repeat the above operation twice to ensure that RhCu M is dispersed in chloroform. After this, 3 mg RhCu M is dispersed in 10 mL chloroform and ultrasonically treated for 5-10 minutes to produce a homogeneous slurry. Then, 10 mgtpp is added to the slurry and treated for another 5 minutes by ultrasonic treatment. Subsequently, the obtained slurry is transferred to a 12 mL sealed glass bottle and then stirred at room temperature for 24 hours. The sediment is collected by centrifugation at 10,000 rpm for 5 minutes, and the supernatant is discarded. Finally, RhCu M-tpp can be obtained after washing the sediment with 10 ml chloroform / ethanol (v / v=1 / 1) solution and centrifuging at 10000 rpm for 5 minutes for several times until the supernatant becomes colorless.

[0120] Heterogeneous rhodium-copper metalloene (RhCu M), rhodium-copper metalloene (Rh M), and copper nanoparticles (Cu NPs) were also investigated to further compare their catalytic performance with that of RhCu M-tpp.

[0121] In a typical synthesis of RhCu M, 3200 μL oleylamine (OAm), 800 μL Rh(acac)3 solution (5 mM in OAm), 400 μL KI solution (40 mM in 1,2-BDO) and 200 μL Cu(acac)2 solution (5 mM in OAm) were mixed together in a 20 mL glass vial and then stirred for 10 minutes. After this, the glass bottle was sealed and subjected to heat treatment in an oil bath at 160 ° C for 12 hours. After cooling to room temperature, the sediment was collected and washed several times with a mixture of n-hexane and ethanol in a volume ratio of 1 / 1. The final product was stored in n-hexane for further use.

[0122] Rh M was synthesized by the same procedure without adding Cu(acac)2 / OAm solution.

[0123] In a typical synthesis of Cu NPs, 10 mL of Cu(acac)2 solution (10 mM in OAm) and 1 mL of 1,2-BDO were added to a 12 mL glass bottle, followed by heat treatment in an oil bath at 140°C for 3 h. Then, Cu NPs can be obtained by centrifugation.

[0124] Example 3

[0125] Characterization of RhCu M and heterogeneous RhCu M-tpp

[0126] XRD measurements were performed on a Rigaku SmartLab SE X-ray diffractometer. Figure 1B , the results showed that RhCu M existed in the form of face-centered cubic (fcc) alloy. After tpp surface modification of RhCu M, RhCuM-tpp was prepared without any identifiable structural changes. The 2θ value of the prepared RhCu M-tpp was 41-42°. The weak and broad diffraction peaks also indicated the low crystallinity and ultrathin characteristics of the material.

[0127] SEM and energy dispersive X-ray spectroscopy (EDS) data were obtained using a Thermo Fisher Scientific (TFS) Quattro S scanning electron microscope. Figure 1C The SEM images showed that RhCu M-tpp exhibited a micrometer-sized self-assembled network and interconnected 2D ultrathin flexible RhCu M-tpp nanosheets. Wrinkles were easily observed on its surface, which was similar to the structure of graphene. EDS data revealed that the corresponding Rh / Cu atomic ratio was nearly 77 / 23 ( Figure 1DThe above observations are similar to those observed for RhCu M, indicating that the effect of TPP modification on the morphology and composition of RhCu metalloene is negligible.

[0128] In addition, the detailed microstructure was investigated by transmission electron microscopy (TEM) and aberration-corrected high-angle annular dark-field scanning TEM (HAADF-STEM). TEM images and electron energy loss spectroscopy (EELS) spectra were collected on a field emission JEM-2100F (JEOL, Japan). HAADF-STEM images and EDS elemental mapping were obtained on a dual-aberration-corrected Spectra 300TEM / STEM equipped with a Super-X EDS spectrometer (Thermo Fisher Scientific, USA (TFS, USA)). Go to Figure 1E The low contrast between the nanosheets and the carbon support indicates the few-layer nature of RhCuM-tpp. The lateral size of the nanosheets is in the range of hundreds of nanometers, while the thickness is below 1 nanometer, which results in a large number of low-coordinated active sites exposed on the surface. Figure 1F As shown in , when compared with RhCu M, the EELS spectrum reveals that RhCu M-tpp exhibits a sharp increase in N signal and a distinct near-edge fine structure of CK. These characteristic signals originate from tpp molecules on the surface of RhCu M-tpp, which are different from the C signal detected in RhCu M due to the carbon coating on the Cu grid and the N signal originating from oleylamine. These observations confirm the presence of tpp molecules on the surface of RhCu M-tpp, a finding further supported by Fourier transform infrared spectroscopy (FT-IR) ( Figure 2 ).

[0129] In addition, low magnification and low dose HAADF-STEM images revealed that the in-plane 2D alloy structure is rich in pits and holes with diameters ranging from 2 nm to 5 nm ( Figures 3A-3D ). A low-dose imaging mode was used to minimize the electron beam damage effect.

[0130] exist Figures 4A-4D In the TEM images, RhCu M-tpp exhibited a heterogeneous structure consisting of crystalline domains and amorphous domains. This structure was further confirmed by the selected area fast Fourier transform (FFT) image. Figures 5A-5D , both the HAADF-STEM images and the corresponding EDS elemental mapping show uniform distribution of Rh, Cu, and N. Similar pits and pores as well as amorphous / crystalline domains were also observed in pristine RhCu M and Rh M.

[0131] The electronic structure and coordination environment of the obtained metalloene were further investigated by X-ray absorption near-edge structure (XANES) and extended X-ray absorption fine structure (EXAFS) spectroscopy. Fig. 6A As shown in , the XANES spectra of RhCu M-tpp and RhCu M at Cu K-edge are similar, where their white line positions fall between those of Cu foil / Cu2O and CuO. This suggests that Cu atoms act as electron donors in both alloy metalloenes due to their weak electronegativity. In contrast, the synthesized Cu NPs show white line positions at slightly higher energy regions than those of RhCu M and RhCu M-tpp, which may be caused by surface oxidation in air. Figure 6B-6C As shown, the EXAFS spectra were Fourier transformed to obtain the local coordination environment of Cu.

[0132] refer to Fig.6D , which is similar to the Cu-Cu scattering path attributed to Cu NP and Cu foil in R space at about Unlike the main peak at , both RhCu M-tpp and RhCu M show their Cu-Cu and / or Cu-Rh scattering paths corresponding to the first shell at about The main peak at . This change in metal-metal bond length indicates the formation of RhCu alloy. After tpp modification, there is a slight change in Cu-Cu and Cu-Rh bond lengths, but the change does not significantly affect the coordination number (CN) of Cu atoms in RhCu M (=9) and RhCuM-tpp (=8.5). Table 1 lists the fitting results of the CuK-edge EXAFS spectra of RhCu M-tpp, RhCu M, Cu NP and Cu foil.

[0133] Table 1

[0134] Go to Figure 7A-7B , RhCu M-tpp and RhCu M show similar graphs of the wavelet transform (WT) of the Cu K-edge EXAFS spectrum, which is different from the graphs of Cu NP, Cu foil and CuO. Compared with RhCu M, the center of the maximum intensity of RhCu M-tpp shows a slight decrease in both the k range and the R range. "k" refers to the range of wave numbers (k), which is generally used to describe the characteristics of EXAFS; "R" refers to the range of distances, which is used to describe the distance between atoms in real space. At the same time, the distribution of the maximum intensity of RhCu M-tpp is narrower than that of RhCu M in the k range. These results indicate that tpp modification leads to some changes in the coordination structure of RhCuM.

[0135] To further elucidate the chemical state of the heterogeneous RhCu M-tpp, X-ray photoelectron spectroscopy (XPS) was performed. XPS analysis was based on a 300 W Al KR radiation (base pressure < 10 -5 mbar) on an ESCALAB 220i-XL electron spectrometer. It is clear that the Rh metal state dominates all synthesized metalloenes. However, both RhCu M-tpp and RhCu M exhibit a much lower proportion of Rh compared to RhM. 3+ ( Figure 8B ).

[0136] A more significant change in the valence state is observed in the high-resolution XPS spectrum of Cu 2p. The two strong peaks at 931.5 eV and 951.5 eV are attributed to metallic Cu. 0 2p 1 / 2 and 2p 3 / 2 The other two weaker doublets at 932.5 / 952.4 eV and 934.2 / 954.1 eV represent the high-valent Cu in RhCu M-tpp. + and Cu 2+ ( Fig. 9A ). Compared with the original RhCu M, the tpp modification induces a slight increase in the Cu valence, which can be attributed to the electron transfer from Cu in RhCu to N in tpp. This change in valence state was further confirmed by Cu LMM Auger electron spectroscopy (AES) characterization ( Fig. 9B ). Such strong electronic coupling was identified as Cu-N bonding, as evidenced by the characteristic peak detected at 399.9 eV in the N1s XPS spectrum ( Fig. 9C ). At the same time, sp appears at about 398.6eV 2 The hybridized C atoms (C=N bonds) further confirmed the existence of tpp in the obtained RhCu M-tpp.

[0137] Example 4

[0138] NO3RR and EOR performance of RhCu M-tpp

[0139] The synthesized RhCu M-tpp catalysts showed potential applications in both electrocatalytic nitrate reduction and electrocatalytic alcohol oxidation to NH3. Specifically, carbon paperboard (1×1 cm, Toray H-060) was used to load a mixture of RhCu M-tpp and Nafion (binder) with a catalyst:binder weight ratio of 5:1 without introducing any carbon conductor. A certain amount of isopropanol was used as a solvent to prepare a catalyst concentration of about 1 mg mL by ultrasonic treatment. -1 The obtained catalyst ink was slowly and uniformly dropped onto carbon paperboard (CP, 1×1 cm, Toray H-060) under ambient conditions. The mass loading was controlled at 0.4 mg cm -2 Up to 0.5 mg cm -2 Inside.

[0140] Linear sweep voltammetry (LSV) measurements were performed in 0.5M Na2SO4 aqueous solution in the absence / presence of 3000ppm NaNO3. NO3 in neutral electrolyte - The low concentration (about 48mM) is relatively close to the NO3 present in industrial wastewater. - concentration, and also significantly reduces CO2 intake problems.

[0141] refer to Fig.10 , in the NO3 - After addition to the electrolyte, both heterogeneous RhCu M-tpp and RhCu M provide much higher current density. The peak current occurring at -0.2V to -0.4V (relative to RHE) is attributed to limited mass transfer. At this stage, both NO3RR and hydrogen evolution reaction (HER) compete, but NO3RR is expected to dominate. When the applied potential becomes more negative (<-0.4V (relative to RHE)), the competitive HER process dominates due to the strong hydrogen evolution ability of Rh. In contrast, with and without NO3RR, the peak current appears at -0.2V to -0.4V (relative to RHE) due to the ... - The differences between the LSV curves of Rh M and Rh M are relatively small. In addition, the synthesized Cu nanoparticles only provide a small current in this potential window.

[0142] The products of NO3RR were analyzed by colorimetry. Fig.11 The NH3 and NO2 of the synthesized samples are shown - RhCu M-tpp provides the best performance in the entire potential window from -0.1 V to -0.5 V (vs. RHE), and achieves an excellent FE of more than 70% at potentials above -0.4 V, and the highest ammonia FE of 84.8% at -0.2 V (vs. RHE). At the same time, a low proportion of NO2 was also detected as a byproduct of NH3 electrosynthesis. -, with FE ranging from 3.4% to 10.9%. In contrast, RhCu M and Rh M exhibited significantly lower catalytic selectivity for NH3 as the potential decreased (FE < 60.3% for RhCu M; FE < 32.6% for Rh M), especially below -0.2 V relative to RHE. For pure CuNPs, NO2 - The production of nitrate dominates the nitrate reduction process, but under the same test conditions, NH3 and NO2 - The total FE is kept at a fairly low level.

[0143] Fig.12 The NH3 production rate of RhCu M-tpp continued to increase with decreasing potential and reached 717.8 mg h -1 g -1 cat The maximum point is nearly 6 times the NH3 production rate of RhCu M. This observation suggests that tpp plays a role in promoting NO3 - Meanwhile, the NH3 production rates of Rh M and Cu NP were even much lower (about 10–30 mg h -1 g -1 cat ), which is mainly due to its low ammonia FE and current density ( Figures 13A-13D Only a few catalysts previously used for NO3RR are able to achieve this highly selective electrosynthesis of NH3 at such low overpotentials under the same conditions.

[0144] Example 5

[0145] Effect of tpp modification on the electrochemically active surface area of ​​RhCu M-tpp

[0146] To obtain the electrochemical surface area (ECSA), CV measurements were performed at different scan rates within the corresponding non-Faraday intervals for different cathodes and the current density difference at the midpoint of the interval (ΔJ, J anodic -J cathodic ) as a function of the scan rate to demonstrate the linear relationship. The slope of the linear relationship is the electrochemical double layer capacitance (C dl ). Then the ECSA can be obtained by the following equation: ECSA=(C dl / C s )×S E , Among them C s Represents specific capacitance (0.04mF cm -2 ), and S E Represents the apparent area of ​​the electrode (1cm 2).

[0147] Go to Figures 14A-14B , at the same mass loading, the C dl 2.79mF cm -2 , the C dl C of RhCu M dl (1.47mF cm -2 ), indicating that more in-plane alloy sites become active for NO3RR after coupling with N atoms of tpp. This result partially explains the significantly higher NH3 production rate of RhCu M-tpp compared with RhCu M.

[0148] It is a well-known fact that TPP itself shows negligible catalytic activity for NH3 electrosynthesis. In order to confirm the origin of nitrogen in the synthesized NH3, isotope labeling experiments were also performed. Fig.15 As shown in the figure, NO3RR is used 14 NO3 - or 15 NO3 - The NH3 production in the electrolyte as nitrogen source is close to each other, as shown by 1 The results were verified by both H nuclear magnetic resonance (NMR) and UV-visible (UV-vis) absorption spectroscopy. In addition, the generation of NH3 was negligible in the absence of added nitrate or when no potential was applied. These results confirm that the NH3 obtained is derived from NO3 - In addition, RhCu M-tpp also showed good catalytic durability for NH3 synthesis ( Fig.16 ). In addition, the morphology, structure, and composition of RhCu M-tpp were well maintained after the cycling stability test.

[0149] Since the formation of NH3 leads to a weak alkaline environment in the electrolyte, the EOR performance of the RhCu M-tpp cathode was further evaluated in solutions containing 1 M KOH and 1 M EtOH. The carbon paper-supported RhCu M-tpp cathode was directly used for EOR measurements to simulate the actual working conditions of NO3RR. Figures 17A-17B Different from the cyclic voltammetry (CV) curves observed in KOH solution, in KOH / EtOH solution, both RhCu M-tpp and RhCu M exhibited two obvious ethanol oxidation peaks at 0.8 V and 0.4 V (vs. RHE). The EOR peak currents of RhCu M and RhCu M-tpp were 34.0 mA mg -1 and 31.8mAmg -1When chronoamperometric electrolysis was performed at 1.0 V (vs. RHE), RhCu M-tpp exhibited higher activity than RhCu M after long-term operation, and the mass activities of RhCu M-tpp and RhCu M at different states were also compared ( Figures 17C-17D ). After EOR measurement, most of the RhCu M-tpp maintained its porous and ultrathin nanostructure, in which both crystalline and amorphous domains still coexisted.

[0150] Replacing ethanol (EtOH) with methanol (MeOH) or ethylene glycol (EG) produced similar effects, lowering the charge plateau of the assembled Zn nitrate / MeOH and Zn nitrate / EG batteries.

[0151] Example 6

[0152] Assembly of zinc nitrate / ethanol batteries and zinc nitrate primary cells

[0153] In view of the excellent electrocatalytic performance of the heterogeneous RhCu M-tpp, a highly rechargeable zinc nitrate / ethanol battery with low overpotential can be constructed.

[0154] During the assembly of the rechargeable zinc nitrate / ethanol cell, a copper-based catalyst (1×1 cm) was used as the working electrode (cathode), while a polished Zn plate (2×2 cm) was used as both the reference electrode and the counter electrode (anode). The RhCu M-tpp cathode was further matched with a Zn metal anode to assemble the zinc nitrate / ethanol cell in a bipolar membrane-separated H-cell, in which 25 ml of a 1 M KOH aqueous solution with 0.02 M Zn(CH3COO)2 as an additive was used as the anolyte, and 25 ml of 0.5 M Na2SO4 / 3000 ppm NO3 mixed with 1 M ethanol was used. - solution as catholyte.

[0155] The assembly of the conventional zinc nitrate primary cell is similar to that of the rechargeable zinc nitrate / ethanol cell above, but only 0.5M Na2SO4 / 3000ppm NO3 is used. - The mixed solution serves as the cathode electrolyte.

[0156] Example 7

[0157] Electrochemical performance of zinc nitrate / ethanol batteries with RhCu M-tpp

[0158] These Zn-based hybrid batteries were subjected to constant current discharge / charge measurements at room temperature under different conditions using a LAND battery test system (CT2001A, Wuhan LAND Co. LTD). The Zn-based hybrid batteries were charged and discharged from a high open circuit voltage (OCV) to 0.005 V (vs. Zn) by 2+ / Zn) is subjected to cathode LSV to obtain the discharge polarization curve, and the resulting power density curve can then be calculated.

[0159] Assembled Zn-NO3 - The cell exhibited an OCV of approximately 1.4 V (vs. Zn 2+ / Zn), which remained stable during the subsequent 24-hour resting period ( Fig.19A ). At the same time, even when the current density reaches up to 2 mA cm -2 (equal to about 5Ag -1 cat ), the battery rate performance can still operate normally ( Fig.19B ).

[0160] Zn-NO3 - Another key technical obstacle facing batteries is their poor rechargeability. Due to the monofunctional design of most previous catalysts used for NO3RR, the assembled Zn-NO3 - Batteries usually function as galvanic cells, which results in sacrificial Zn plates. Renewing the anode electrolyte and Zn anode from the packaged battery device requires another complex production line, which involves a large amount of energy input and cumbersome operations. This feature is not conducive to the deployment of Zn-NO3 in grid-level energy storage or electric transportation facilities. - Batteries. In order to overcome this weakness, attempts have been made to carry out the oxygen evolution reaction (OER) at the cathode side to provide electrons for zinc deposition on the anode. However, most catalysts with good electrocatalytic activity for NO3RR are not suitable for OER and are unstable for OER, which makes the battery non-rechargeable or has a large charging plateau and a rather limited cycle life. At the same time, if the only benefit of OER is to recharge the battery, then this is not energy economical, and in a sealed power unit, there may be several potential safety hazards such as high voltage, fire and explosion due to the generated O2 gas. Unfortunately, there is still a lack of effective bifunctional catalysts and electrochemical systems to build high-performance, rechargeable and eco-friendly Zn-NO3 - Hybrid energy conversion and storage device.

[0161] Compared to commercial non-rechargeable Zn-NO3 which requires a high charging potential to drive the oxygen evolution reaction for recharging -Compared with the conventional batteries, in the present invention, the Rh in RhCu M-tpp not only promotes proton enrichment around the Cu sites in NO3RR (discharge process), but also acts as an active site for EOR (charge process) to provide electrons for reversible Zn insertion on the anode.

[0162] EOR for Metal-NO3 - The energy efficiency of the cell is greater than that of the oxygen evolution reaction, as evidenced by lower overpotential, desirable products and extended lifetime. A mixed solution containing 0.5 M Na2SO4, 3000 ppm NaNO3 and 1 M ethanol was used as the catholyte. Figures 20A-20B , according to the OCV and rate performance of the zinc nitrate / ethanol battery assembled in this way, the addition of ethanol does not affect the electrochemical behavior of the catalyst in NO3RR.

[0163] The apparent performance of Cu nanoparticles mainly comes from the production of NO2 - reaction and self-reduction rather than the formation of NH3. Fig.21A Figure 2 shows the rate performance of the heterogeneous RhCu M-tpp and Cu NP cathodes during discharge. -2 , 0.2mA cm -2 , 0.5mA cm -2 , 0.8 mA cm -2 , 1.0mA cm -2 , 1.5mA cm -2 and 2.0mA cm -2 The discharge platforms under the conditions were approximately 1.36 V, 1.28 V, 1.07 V, 0.69 V, 0.52 V, 0.41 V and 0.34 V (relative to Zn 2+ / Zn), which is significantly higher than the discharge platform of CuNP. When the battery resumes operation at a low rate, its operating voltage returns to its original state, indicating that RhCuM-tpp has excellent tolerance to high current shocks.

[0164] refer to Fig. 21B The constructed ZnNO3 / ethanol battery with RhCu M-tpp exhibited a high charge / discharge rate at 0.5 mA cm -2 Fully discharged to 0.005V (relative to Zn 2+ / Zn) released a total of 50.82 mWh of excellent electrical energy, which corresponds to 117364.6 Wh kg -1 cat It also provides 0.1mA cm -2Considering the enhanced NO3RR kinetics, the ZnNO3 / ethanol battery with RhCu M-tpp achieved 1.54 mW cm -2 The maximum power density is the power density of Cu NP (0.38 mW cm -2 )4 times more ( Fig. 21C ).

[0165] In addition, cathodic LSV measurements were performed from OCV to 1.85 V (vs. RHE) on a RhCu M-tpp cathode after 1 h of NH3 electrosynthesis in different electrolytes with or without ethanol. Fig.21D It is shown that during the linear scan, in the absence of ethanol, many bubbles are formed on the cathode surface, while in the solution containing ethanol, no noticeable bubble formation is observed on the other cathode surfaces. This indicates that OER and EOR occur in two different electrolytes, respectively. Meanwhile, on the RhCu M-tpp cathode, at the same current density, EOR exhibits a much lower overpotential than that of OER. Fig. 22 shows the 1 mA cm for battery operation -2 At a typical current density of , the voltage gap reaches 424 mV, close to the maximum value of 443 mV, which means that the energy consumption will be greatly reduced when charging this battery with EOR instead of OER.

[0166] Then, the zinc nitrate / ethanol battery was continuously discharged and recharged at different rates. -2 Increase to 2 mA cm -2 , a gradual voltage polarization occurred during both the discharge and charge processes, and the cell voltage returned to 0.1 mA cm -2 After recovery, and in the subsequent cycles at 1 mA cm -2 This indicates that RhCu M-tpp has good chemical and structural stability as a bifunctional catalyst ( Fig.23A During the rate performance measurements, the highest round-trip energy efficiency was 76.9% ( Figures 23B-23C ). In addition, the long-term cycling performance in different electrolytes was also evaluated.

[0167] Compared with conventional Zn-NO3 - The primary cell, a rechargeable zinc nitrate / ethanol battery, showed a high charge / discharge rate at 0.1 mA cm -2 The battery can be charged to a maximum of 130mV and maintain normal function for more than 40 hours. Fig.23D ). In addition, when 0.5 mA cm -2When running at a higher rate, it stably lasts for at least 400 cycles ( Fig.23E ).

[0168] refer to Figures 24A-24D ,use 1 The H NMR quantitative method was used to further investigate the changes in the concentration of acetic acid (HAc) in the cathode electrolyte during the cycles. According to the test results, the concentrations of HAc in the electrolyte were calculated to be 173.86 mg L-1 at the 50th, 100th, 150th, 200th, 250th, and 300th cycles, respectively. -1 、257.70mg L -1 、311.90mg L -1 、349.52mg L -1 、367.78mg L -1 and 408.15 mg L -1 At the selected cycles, the corresponding energy efficiencies of the zinc nitrate / ethanol battery were 71.88%, 48.97%, 48.47%, 47.45%, 47.85%, and 47.17%, respectively. With the accumulation of cycles, the rate of increase of HAc concentration decreased at every 50 cycles.

[0169] In addition, as a combination of NO3RR and EOR products, ammonium acetate, a chemical widely used in various important fields ( Fig.25 ).

[0170] refer to Figures 26A-26D TEM, EDS, and XPS characterizations revealed that RhCu M-tpp maintained its microstructure and surface chemistry throughout the long-term round-trip NO3RR-EOR cycle, even after passivation.

[0171] In general, except for parasitic reactions such as HER and OER, the reasonable working principle of the thus fabricated zinc nitrate / ethanol battery can be described as follows: anode: cathode C2H5OH+4OH - →CH3COOH+3H2O+4e - (Charge) Overall reaction: 4ZnO+2C2H5OH→4Zn+2CH3COOH+2H2O (Charging)

[0172] Example 8

[0173] Mechanism of molecule-metal relay catalysis

[0174] To gain a deeper understanding of the enhanced catalytic performance of heterogeneous RhCu M-tpp for NH3 electrosynthesis, systematic ex situ / in situ analysis and characterization were performed. Ex situ / in situ experimental studies and theoretical calculations revealed the existence of molecule-metal relay catalysis on RhCu M-tpp in NO3RR, which significantly promoted ammonia selectivity and reaction kinetics through a low-barrier pathway.

[0175] Fig.27A It is shown that, in the entire potential window from -0.1 V to -0.5 V (vs. RHE), on the pure tpp electrode, NO2 - The dominant reduction product, while the formation of NH3 is greatly promoted on the RhCu M electrode. Significantly, the combination of tpp and RhCu alloying sites leads to a higher selectivity for NH3 production on the RhCu M-tpp cathode compared to the RhCu M counterpart. Moreover, even when the NO3RR rate is normalized with respect to the ECSA ( Fig.27B ), compared with RhCu M, RhCu M-tpp still exhibits faster electron consumption to convert NO3 in a wide potential range. - This indicates that the reaction kinetics on the individual active sites are significantly enhanced. The above results indicate that there is a molecule-metal relay catalysis between the tpp alloying sites and the RhCu alloying sites, where the transformation order is:

[0176] NO3 - First adsorbed and then reduced to NO2 at a moderate reaction rate on TPP - , then NO2 - diffuse to the Cu site for subsequent rapid hydrogenation for NH3 production assisted by surrounding Rh atoms. Meanwhile, based on in situ differential electrochemical mass spectrometry (DEMS) and H2 quantification results ( Figures 28A-28D ), the presence of tpp molecules on the RuCu metalloene surface can also help suppress the formation of H2 (the main gas byproduct) around the Rh center under low overpotential conditions.

[0177] exist Fig.29 In the present study, Kelvin probe force microscopy (KPFM) characterization revealed an inhomogeneous potential distribution in the 3D assembly of synthesized RhCu M-tpp, where the metalene junction provides a higher potential than the in-plane nanosheet. Based on the potential line scan of a typical metalene assembly, the potential gap was estimated to be about 36.6 mV ( Fig.30 ). Therefore, it can be inferred that multiple directional electric fields are established, which span from the junction to the edge of the nanosheet under the applied potential in each individual metal ene. The gradient distribution of the electric field can promote ion migration and adsorption / desorption of intermediates on the catalyst surface, thereby promoting the reaction kinetics of NO3RR.

[0178] Example 9

[0179] Electrochemical mechanisms of NO3RR and EOR of RhCuM-tpp

[0180] In this example, in situ DEMS was used to clarify the reaction intermediates and products of a zinc nitrate / ethanol battery. Fig.31A , at 6mV s -1 During four cathodic linear scans from 0 V to -0.66 V (vs. RHE) at 100 Hz, two distinct signals with mass-to-charge (m / z) ratios of 2 and 17 were detected over the reaction time. These signals correspond to the formation of H2 and NH3 at negative potentials, respectively. However, no signals of NH2OH (m / z = 33) and NO2 (m / z = 46) intermediates were detected on the NO3RR side. This absence can be attributed to the extremely rapid hydrogenation process occurring on this molecule-metal relay catalyst. At the EOR side, there was no obvious fluctuation in the NH3 signal ( Fig.31B ), indicating that NH3 cannot be oxidized under four anodic linear sweeps from 0.551 V to 1.6 V (vs. RHE). This observation reveals the feasibility of subsequent alcohol oxidation to produce ammonium acetate. Only a very small amount of O2 (m / z=32) was identified at the first cycle of LSV, indicating that EOR is the dominant reaction rather than OER when charging the battery. Acetaldehyde (CH3CHO, m / z=44) and acetic acid (CH3COOH, m / z=60) were also detected as the dominant intermediates and final products of EOR.

[0181] In addition, according to the in situ DEMS results obtained during the sequential cathode and anode linear scanning cycles ( Fig.32 ), the OH produced in the previous NO3RR - It plays an important role in maintaining the subsequent catalytic activity of RhCu M-tpp for EOR during discharge-charge cycles. 6 The above online round-trip monitoring results thoroughly explain the detailed electrochemical reactions occurring during the discharge and charge processes of the assembled zinc nitrate / ethanol battery.

[0182] Example 10

[0183] Computational Research

[0184] To better understand the improvement in electroactivity, DFT calculations were performed to study the electronic modulation induced by the surface tpp molecules. Considering the computational load, a single tpp (transition path sampling) building unit was incorporated at the interface between crystalline RhCu and amorphous RhCu. For the electron distribution close to the Fermi level (EF), it was observed that the interface region and surface tpp dominated the bonding orbitals of the RhCu M-tpp surface, which acted as the main active sites. Compared to RhCu M, the bonding orbitals became stronger at the interface between the crystalline and amorphous regions, which supports the increase of active sites for NO3RR ( Figures 33A-33B ). Coverage of TPP molecules on the surface activates the electroactivity of the surface regions, thereby providing more accessible active sites. These results indicate that rich crystalline-amorphous interfaces and surface TPP modification are important to ensure highly electroactive surfaces and efficient electron transfer efficiency from catalyst to adsorbate. The interface remains stable after geometry optimization, indicating that the stability of the catalyst is generally good.

[0185] To reveal the electronic structure, the projected partial-wave density of states (PDOS) ( Fig.33C ). The Cu-3d orbital is located at E V Near -2.18eV (Ev = 0eV), the orbital coupling with Rh-4d orbital is good. At the same time, Rh-4d orbital covers Cu-3d orbital and crosses e g -t 2g Split into 2.97 eV E F , to promote electron transfer. This electronic structure supplies highly robust electroactivity of active sites during NO3RR. The introduction of surface tpp not only enhances E F The electron density nearby accelerates the electron transfer, and also provides a wide p orbital distribution to improve the NO3 - The adsorption of NO3 - Strong adsorption on the surface tpp ( Fig.33D ). Significantly, NO3 - The s,p orbitals of RhCu M-tpp are shifted downward, which supports the electron transfer from RhCu M-tpp to the adsorbate. - We observed good overlap of the s and p orbitals with the tpp molecule, especially near E V -6.0eV to E V At -8.0 eV, this induces NO3 - The stable binding and activation of RhCu accelerates the following reduction step. For the Cu sites in the crystalline RhCu part, the Cu-3d orbital exhibits a gradual upward shift from the bulk to the surface, which leads to an increase in the d-band center and electrical activity.

[0186] Specifically, it was observed that the introduction of tpp shifted the Cu-3d orbital upward, which is consistent with the XPS results showing a slight increase in the valence state of the Cu site ( Fig.33E ). The electronic structure evolution of Cu-3d becomes even stronger in the amorphous part. The bulk Cu-3d shows a position significantly lower than that of the surface Cu sites. However, the Cu-3d orbital is located closer to the EF in the amorphous part than in the crystalline part, which indicates that the amorphous part plays an important role in promoting the electroactivity of the surface interface region. For the Rh-4d orbital in the crystalline structure, the e g -t 2g The splitting gradually decreases from the bulk to the surface. After the introduction of tpp, as the E F The electron density is enhanced, e g -t 2g The splitting is significantly reduced, which enables faster site-to-site electron transfer in RhCu M-tpp. For the amorphous part, the e of the Rh-4d orbital is g -t 2g The splitting provides a volcano-type trend that first increases at the surface and decreases at the interfacial site with tpp. This demonstrates the key role of surface modification using tpp in promoting electron transfer on the RhCu M catalyst.

[0187] refer to Fig.33F , the reaction energies of NO3RR between RhCu M-tpp and RhCu M were compared to emphasize the importance of tpp. Significantly, the introduction of tpp on the RhCu M catalyst resulted in an increase in the conversion of nitrate to NO2 * The activation barrier of RhCu M-tpp and RhCu M was reduced from 0.57 eV to 0.26 eV. * Converted to NO * The largest energy barrier was observed in RhCu M. * To NH2 * , which largely reduced the electrocatalytic performance. In contrast, RhCu M-tpp only showed an upward trend from NHO * The energy barrier becomes a tiny one of 0.28 eV for NH2O, which supports highly efficient nitrate reduction. In addition, the desorption of the generated NH3 shows an energy barrier of only 0.13 eV on RhCu M-tpp, which is much smaller than that on RhCu M (0.50 eV), thus enabling rapid generation of NH3.

[0188] In order to reveal the reaction trend of NO3RR, the adsorption energies of different key intermediates on different sites of RhCu M-tpp were compared, such as Figure 33G and as shown in Table 2.

[0189] Table 2-NO3 * 、NO2 * 、NO * NH3 * and H2O * Adsorption energy on different sites of RhCu M-tpp.

[0190] In order to reveal the reaction trend of NO3RR, the adsorption energies of different key intermediates on different sites of RhCu M-tpp were compared. Figure 33G ). For the initial reactants, NO3 - Both NO and H2O tend to adsorb on the tpp site, which is conducive to the activation of nitrate and the dissociation of water. * and NO * The adsorption of becomes more energetically favorable on the amorphous sites and interfacial sites on the catalyst surface, respectively, suggesting that the subsequent nitrate reduction process is promoted on the RhCu surface. The adsorption results support that the nitrate reduction process on RhCu M-tpp is potentially a cascade catalysis, in which the surface tpp ensures the activation of nitrate, while RhCu acts as a catalyst for NO2 - It becomes the active site for the subsequent reduction of the final product NH3.

[0191] Example 11

[0192] Application of zinc nitrate / ethanol batteries with RhCu M-tpp

[0193] To demonstrate the potential in consumer electronics, the assembled zinc nitrate / ethanol battery was used to power a commercial digital clock for more than 24 hours ( Fig.34 ).

[0194] Table 4 shows the comprehensive performance comparison between the zinc nitrate / ethanol (Zn-NO3RR / EOR) battery assembled in this way and other representative zinc-based hybrid energy storage systems. The results show that compared with the zinc nitrate / ethanol battery fabricated in this way, the previously reported Zn-based aqueous batteries rarely exhibit such comprehensive performance and multifunctionality.

[0195] In Table 4, "Functionality" indicates the number of functions (as shown below) possessed by the mentioned zinc-based aqueous battery: (A) electricity supply, (B) electrosynthesis of NH3, (C) electrosynthesis of carbon products, (D) electrosynthesis of organic ammine compounds, (E) carbon neutrality, (F) sewage treatment. For illustration, the following are the detailed functions and ease of charging of the mentioned Zn-based aqueous batteries: Zn-NO3RR / EOR ​​battery [present invention]: Functionality - (A) (B) (D) (F) Zn-NO3RR battery: Functionality - (A) (B) (F) Zn-NO3RR / OER battery: Functionality - (A) (B) (F) Zn-NO2RR battery: Functionality - (A) (B) (F) Zn-Air(O2) Battery: Functionality-(A) Zn-CO2 / FAO battery: Functionality - (A) (C) (E) Zn-N2 / OER battery: Functionality-(A)(B)

[0196] In addition, “rechargeability” indicates the ease of charging the mentioned Zn-based aqueous battery based on the following criteria: (0) non-rechargeable, (1) optimal discharge-charge overpotential gap (OOP) > 2 V, (2) 1.5 V <OOP<2V,(3)1V<OOP<1.5V,(4)0.5V<OOP<1V,(5)OOP<0.5V。

[0197] Table 4 “N / A” indicates that no data were available in the literature.

[0198] The foregoing description of the present invention has been provided for the purpose of illustration and description. The foregoing description is not intended to be exhaustive or to limit the present invention to the precise form disclosed. Many modifications and variations will be apparent to those skilled in the art.

[0199] The embodiment was chosen and described in order to best explain the principles of the invention and its practical application, thereby enabling others skilled in the art to understand the invention for various embodiments and with various modifications as are suited to the particular use contemplated.

[0200] Industrial Applicability:

[0201] The present invention provides a highly efficient bifunctional catalyst of porous heterogeneous RhCu M-tpp for low overpotential NH3 electrosynthesis and ethanol oxidation. A molecular-metal relay catalytic mechanism exists in nitrate reduction on RhCu M-tpp, which significantly promotes reaction kinetics and selectivity through a low energy barrier pathway.

[0202] The present invention not only highlights the importance of molecular-metal relay catalysis for efficient NH3 electrosynthesis in NO3RR, but also presents a multifunctional battery prototype to demonstrate the advantages of metal-based hybrid electrochemical systems for high-performance and sustainable energy storage and conversion. Zinc nitrate batteries represent an ideal electrochemical source candidate with these favorable properties, which has great potential in the fields of clean energy, catalysis, fine chemical engineering, electronic devices, etc. The main potential markets of the present invention include power sources for electric transportation vehicles and stationary energy storage devices.

[0203] definition

[0204] Throughout this specification, unless the context requires otherwise, the word "comprise" or variations such as "comprises" or "comprising" should be understood to imply the inclusion of the stated integer or groups of integers, but not the exclusion of any other integer or groups of integers. It should also be noted that in this disclosure and particularly in the claims and / or paragraphs, terms such as "comprises", "comprised", "comprising" and the like may have the meaning ascribed to them in U.S. patent law; for example, such that it allows elements not expressly recited, but excludes elements found in the prior art or elements that affect the basic or novel characteristics of the invention.

[0205] Furthermore, throughout the specification and claims, unless the context requires otherwise, the word "include" or variations such as "includes" or "including", will be understood to imply the inclusion of a stated integer or group of integers but not the exclusion of any other integer or group of integers.

[0206] As used herein and not otherwise defined, the terms "substantially," "substantially," "approximately," and "about" are used to describe and explain small variations. When used in conjunction with an event or circumstance, the terms may encompass instances where the event or circumstance occurs precisely as well as instances where the event or circumstance occurs close to occurring. For example, when used in conjunction with a numerical value, the terms may encompass a range of variation less than or equal to ±10% of the numerical value, such as less than or equal to ±5%, less than or equal to ±4%, less than or equal to ±3%, less than or equal to ±2%, less than or equal to ±1%, less than or equal to ±0.5%, less than or equal to ±0.1%, or less than or equal to ±0.05%.

[0207] References in this specification to "one embodiment", "an embodiment", "example embodiment", etc. indicate that the described embodiment may include a particular feature, structure, or characteristic, but not every embodiment necessarily includes the particular feature, structure, or characteristic. In addition, such phrases do not necessarily refer to the same embodiment. Further, when a particular feature, structure, or characteristic is described in conjunction with an embodiment, it is considered to be within the knowledge of those skilled in the art to affect such feature, structure, or characteristic in conjunction with other embodiments, whether or not explicitly described.

[0208] In the preparation method described herein, except for the case of explicitly describing the time or operation sequence, the steps can be performed in any order without departing from the principles of the present invention. The description of performing a certain step first and then performing several other steps subsequently in a certain claim should be considered to mean that the first step is performed before any other steps, but the other steps can be performed in any suitable order unless the order is further described in other steps. For example, the claim element describing "step A, step B, step C, step D and step E" should be interpreted as meaning that step A is performed first and step E is performed last, and steps B, C and D can be performed in any order between step A and step E, and the order still falls within the literal scope of the process claimed for protection. A given step or a subset of steps can also be repeated. In addition, unless the clear claim language describes that the specified steps are performed separately, the specified steps can be performed simultaneously.

[0209] "RhCu metalloene" refers to a metal compound composed of rhodium (Rh) and copper (Cu). In the present invention, it is an amorphous / crystalline RhCu metallo compound formed by slow co-reduction of a Rh precursor and a Cu precursor in an amine compound such as oleylamine.

[0210] "Tetraphenylporphyrin (TPP)" is an organic compound belonging to the class of porphyrin compounds. It consists of four phenyl groups connected to each other, forming a planar ring with four nitrogen atoms at the center. TPP is widely used in biochemistry and organic synthesis, especially as a photosensitizer, catalyst and molecular recognition tool.

[0211] The term "reversible hydrogen electrode (RHE)" is a reference electrode commonly used in electrochemistry. It is based on hydrogen gas, and under standard conditions (1 atm H2, 25°C), its potential is defined as 0 V. RHE provides a stable reference potential for measuring the potentials of other electrodes.

[0212] The term "bipolar membrane" refers to a specialized membrane commonly used in electrochemical applications that can split water into hydrogen and oxygen while separating hydrogen ions and hydroxide ions.

[0213] Other definitions of selected terms used herein may be present in the detailed description of the present invention and are applicable throughout the text. Unless otherwise defined, all other technical terms used herein have the same meaning as those generally understood by those of ordinary skill in the art to which the present invention belongs.

[0214] References: The disclosures of the following references are incorporated by reference 1. Y. Guo et al., Pd doping-weakened intermediate adsorption to promote electrocatalytic nitrate reduction on TiO2 nanoarrays for ammonia production and energy supply with zinc-nitrate batteries. Energy Environ. Sci., 14, 3938-3944 (2021). 2. W. Sun et al., A rechargeable zinc-air battery based on zinc peroxide chemistry. Science 371, 46-51 (2021). 3. Guo, Ying et al. "Pd-doping weakened intermediate adsorption promotes electrocatalytic nitrate reduction on TiO2 nanoarrays for ammonia production and energy supply in zinc nitrate batteries." Energy & Environmental Science 14.7(2021): 3938-3944. 4. W. He et al., Splicing the active phases of copper / cobalt-based catalysts achieves high-rate tandem electroreduction of nitrate to ammonia. Nature Communications, 13, 1129 (2022). 5. Y. Wang, W. Zhou, R. Jia, Y. Yu, B. Zhang, Unveiling the activity origin of a copper-based electrocatalyst for selective nitrate reduction to ammonia. Angew. Chem. Int. Ed. 59, 5350-5354 (2020). 6.YQ Kang et al., Selective etching induced synthesis of hollow Rh nanosphere electrocatalyst for alcohol oxidation reactions. Small, 14, 1801239 (2018).

Claims

1. A rechargeable zinc nitrate / ethanol battery comprising: a cathode comprising a conductive substrate coated with one or more copper-based catalysts having a heterogeneous structure; anode; a separator disposed between the cathode and the anode; Anolyte, the anolyte is located on the anode side; as well as a catholyte, the catholyte being located on the cathode side, wherein the rechargeable zinc nitrate / ethanol battery exhibits at least 110,000 Wh kg -1 cat Energy density of at least 1.5 mW cm -2 The power density is as high as 1000 cycles and the long-term cycling stability is about 400 cycles.

2. The rechargeable zinc nitrate / ethanol battery of claim 1, wherein the one or more copper-based catalysts comprise a tetraphenylporphyrin-modified rhodium-copper alloy metalloene having a 2θ value of 41-42°.

3. The rechargeable zinc nitrate / ethanol battery of claim 2, wherein the tetraphenylporphyrin-modified rhodium-copper alloy metalloene comprises 60-85 wt% Rh and 15-40 wt% Cu.

4. The rechargeable zinc nitrate / ethanol battery of claim 2, wherein the tetraphenylporphyrin-modified rhodium-copper alloy metalloene exhibits micrometer-sized self-assembled networks with interconnected two-dimensional flexible nanosheets.

5. The rechargeable zinc nitrate / ethanol battery of claim 2, wherein at a low overpotential of less than -0.1 V, NO3 - Converted into NH3, the NO3 - First adsorbed and then reduced to NO2 on tetraphenylporphyrin - , and then NO2 - diffuses to the Cu site for subsequent hydrogenation process for NH3 production assisted by surrounding Rh atoms.

6. The rechargeable zinc nitrate / ethanol battery of claim 5, wherein the NH3 generation rate of the tetraphenylporphyrin-modified rhodium-copper alloy metalloene increases as the potential decreases, and the NH3 generation rate is 6 times the NH3 generation rate of the unmodified rhodium-copper alloy metalloene.

7. The rechargeable zinc nitrate / ethanol battery according to claim 2, wherein the tetraphenylporphyrin-modified rhodium-copper alloy metalloene exhibits two ethanol oxidation peaks at 0.8 V and 0.4 V compared to a reversible hydrogen electrode in an alkaline solution with an alcohol, wherein the alcohol includes EtOH, MeOH or ethylene glycol.

8. The rechargeable zinc nitrate / ethanol battery of claim 2, wherein the tetraphenylporphyrin-modified rhodium-copper alloy metalloene achieves an ammonia faradaic efficiency of at least 70% at a potential above -0.4V.

9. The rechargeable zinc nitrate / ethanol battery of claim 1, wherein the zinc nitrate / ethanol battery exhibits a -2 The lower charging plateau is reduced by approximately 130 mV and normal function is maintained for at least 40 hours.

10. The rechargeable zinc nitrate / ethanol battery of claim 1, wherein the conductive substrate comprises conductive carbon cloth or a glassy carbon electrode.

11. The rechargeable zinc nitrate / ethanol cell of claim 1 , wherein the anode comprises a zinc plate.

12. The rechargeable zinc nitrate / ethanol battery of claim 1, wherein the separator comprises a bipolar membrane.

13. The rechargeable zinc nitrate / ethanol battery of claim 1, wherein the anolyte comprises a 1M KOH aqueous solution having 0.02M Zn(CH3COO)2, and the catholyte comprises 0.5M Na2SO4 / 3000ppm NO3 - A mixture of solution and 1 M ethanol.

14. The rechargeable zinc nitrate / ethanol battery of claim 1, wherein the heterogeneous structure comprises crystalline domains and amorphous domains.

15. A method for synthesizing heterogeneous tetraphenylporphyrin-modified rhodium-copper alloy metalloene, the method comprising Co-reducing a rhodium precursor and a copper precursor in an oleylamine solution to obtain a RhCu metalloene, wherein the feed ratio of the Rh precursor to the Cu precursor is 8:1; adding at least one reducing agent and at least one surfactant to surface modify the RhCu metalloene; heating the RhCu metalloene in an oil bath at 160° C. for 12 hours to obtain a modified RhCu metalloene; and The modified RhCu metalloene is subjected to ligand exchange in chloroform in which tetraphenylporphyrin is dissolved, and centrifuged at 10,000 rpm for 5 minutes to obtain the heterogeneous tetraphenylporphyrin-modified rhodium-copper alloy metalloene, The thickness of the heterogeneous tetraphenylporphyrin-modified rhodium-copper alloy metalloene is in the range of 0.01 nm to 1 nm. 16 . The method according to claim 15 , wherein the tetraphenylporphyrin-modified rhodium-copper alloy metalloene comprises 60-85 wt % of Rh and 15-40 wt % of Cu, and an element ratio of the Rh to the Cu is 4:

1.

17. The method of claim 15, wherein the at least one reducing agent comprises 1,2-butanediol and the at least one surfactant comprises potassium iodide.

18. The method of claim 15, wherein the ratio of the RhCu M to the tetraphenylporphyrin is 95:

5.

19. The method of claim 15, wherein the heating is performed at a reaction temperature ranging from 155°C to 180°C.

20. The method of claim 15, wherein the concentration of the tetraphenylporphyrin is in the range of 5 mM to 100 mM.